Comparison of tectonic elements of the crust with oil and gas structures in the Karkinit trough - Kozlenko, M.V.; Kozlenko, Yu.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
Based on the analysis of features of the position of tectonic elements relative to fields and unproductive areas, it has been suggested about the prospects of the local structures of the sedimentary cover on the presence of hydrocarbons. It is determined that, for hydrocarbon accumulations, the proximity to the rift and the concurrent faults is necessary. First and foremost, the structures that meet both criteria are attractive, the second - related to rifting zones, but not backed by tectonic faults.